Love and rockets the sketchbooks - Hernandez, Gilbert 1957-; Hernandez, Jaime 1959- (Fantagraphics, 2024)
"Behind the scenes with the Brothers Hernandez. A trove of rarely-seen artwork, spanning 1977-1991: early short comics, fan art, magazine illustrations, punk flyers, unused Love & Rockets pages, covers & sketches, and hundreds of drawing from the private notebooks of Jaime and Gilbert Hernandez"--Back cover
Two works bound together back-to-back and inverted. Tête-bêche format
Keywords: Comic books, strips, etc / United States / History / 20th century; Caricatures and cartoons / United States / History / 20th century; Comic books, strips, etc / Authorship; Drawing / United States / Technique; Comics (Graphic works); Comic